Workshop Sistem Informasi Geografis (SIG): Peningkatan Kapasitas Petugas Surveilans Puskesmas di Wilayah Kabupaten Gunung Kidul dalam Pembuatan Peta Sebaran Penyakit - M Syairaji; Ismil Khairi Lubis (Jurnal Pengabdian dan Pengembangan Masyarakat, 2019)
One of surveillance quality is the data should be usefull for prevention and disease control as wellas detecting pattern or trend. This only can be done if the data have analyzed. Map is one of dataanalyzing which is important to draw disease distribution. In this training, Primarly health caresurveillance officer are expected to know and able to make simple map with GeospatialInformation System (GIS) software. This activity is software using training using free software epiinfo version 7.2 by CDC where previously the participants have given brief material about GIS inthe field of health. Observation was conduct to see if there are increasing of skill for makingdigital map. The participants also given a modul to help them re-learning after completion of theactivity. Based on the observation during training, participant looked enthusiastic and active inasking questions. For observation results, it showed increasing 100% of skill for creating mapswhereareas berfore workshop there are no participant who experienced for making digital maps.Over all, this training is effective to provide refreshing and knowledge in the field of informationtechnology that supports health data processing and analyzing in Puskesmas.